The Capitalocene and Slow Violence in Gabriel García Márquez’s One Hundred Years of Solitude - Gülter, Işıl Şahin (Karadeniz Technical University, 2023)
The term Global South originates in the social sciences, where it invokes the notion of a global North-South divide to organize nations according to socioeconomic and political status. In a literary context, the Global South signifies an ongoing endeavor to engage with the current global disposition by identifying its externalities and providing the framework in which wide-ranging and cross-regional resistance might be imagined. Drawing on this point of view, the Global South can be regarded as a resilient political imagination originating from the marginalized peoples’ mutual recognition of analogous circumstances under contemporary capitalism. Recognition is, therefore, the critical point for the construction of Global South consciousness, which will enable those people to activate solidarities that can be put into action toward the goal of liberation. In this context, this paper intends to investigate Gabriel García Márquez’s portrayal of an environmental apocalypse in One Hundred Years of Solitude (1967), which offers rich possibilities for thinking about García Márquez in relation to the Global South. Paying particular attention to the geographical vulnerability of the Global South and Márquez’s representation of the transnational banana company’s ecocidal practices in Macondo, this paper establishes an analogous connection between capitalism’s externalities and its impact on the environmental degradation and the living conditions of local communities. Drawing heavily on Jason W. Moore’s notion of “the Capitalocene” and Rob Nixon’s theory of “slow violence,” this paper indicates that One Hundred Years of Solitude highlights the intersections between the analogous deterioration of the poor people’s living conditions and the environment in Macondo, offering multiple entry points from which socio-ecological connections are embodied and conveyed to the readers. © 2023 Karadeniz Technical University. All rights reserved.
Keywords: Anthropocene; Capitalocene; Gabriel García Márquez; Global South; One Hundred Years of Solitude; slow violence